SOCIO-ECONOMIC AND CULTURAL LIFE OF KHIVA KHANATE - Ashirov B.M (Ethiopian International Journal of Multidisciplinary Research, 2025)
The largest city of Khorezm or the Khiva Khanate was Khiva (modern Uzbekistan) — its capital from the beginning of the 17th century until 1920. In ancient times, the city was called Khiyvak. Since its foundation, Khiva was a link on the trade route between the East and the West. At the beginning of the 17th century, due to a change in the course of the Amu Darya, unfavorable living conditions for the population developed in the capital of the khanate, Urgench, and the capital was moved to Khiva. New Urgench was built under Abulgazi Khan in the 17th century. After that, ancient Urgench began to be called Kunya-Urgench. It contains the mausoleum of Fakhriddin Razi of 12th-14th centuries, the mausoleum of Sultan-Tekesh, Nazhmitdin-Kubro, a cathedral mosque, a minaret and the remains of caravanserais. New Urgench is the center of the current Khorezm region.